EFEKTIVITAS INKLUSI KEUANGAN SYARIAH DALAM MENINGKATKAN PEMBERDAYAAN UMKM (STUDI PADA BMT AL-ISHLAH KOTA JAMBI) - Deby Vebriyani; Ahmad Syahrizal; Fauzan Ramli (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to evaluate the effectiveness of Islamic financial inclusion implemented by BMT Al-Ishlah Jambi in improving the empowerment of Micro, Small, and Medium Enterprises (MSMEs). The approach of this research is qualitative, with a phenomenological method that relies on primary data from the results of interviews, observations, and documentation. This research was conducted at BMT Al-Ishlah Jambi, with the object of the research including BMT staff and MSME members who received funding. The results of the study show that the inclusion of Islamic finance implemented by BMT Al-Ishlah is effective in increasing the empowerment of MSMEs. This can be seen from the increase in income and service quality for MSME members who have received funding. This finding is expected to contribute to the development of sharia financial inclusion theory and become a practical reference for financial institutions in community economic empowerment